Scanning Probe Microscopy in Assessing Blood Cells Roughness - Sovetnikov T. O. Timofei Olegovich; Akhmetova A. I. Assel Iosifovna; Gukasov V. M. Vadim Mikhaylovich; Evtushenko G. S. Gennady Sergeevich; Rybakov Yu. L. Yury Leonidovich; Yaminskii I. V. (2023, 2023)
Title screen